2010
DOI: 10.1021/ja106272z
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hybrid Organic−Inorganic Catalytic Materials with a Hierarchical System of Well-Defined Micro- and Mesopores

Abstract: Novel layered zeolitic organic−inorganic materials (MWW-BTEB) have been synthesized by intercalation and stabilization of arylic silsesquioxane molecules between inorganic zeolitic MWW layers. The organic linkers are conformed by two condensed silyl-arylic groups from disilane molecules, such as 1,4-bis(triethoxysilyl)benzene (BTEB), which react with the external silanol groups of the zeolitic layers. The hybrids contain micropores within the inorganic layers and a well-defined mesoporous system in between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
195
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(203 citation statements)
references
References 39 publications
3
195
0
1
Order By: Relevance
“…There is much interest in the design of hybrid materials for selective and multi-step catalytic processes 1 . In this field, Metal-Organic Frameworks (MOFs) can play an important role due to the possibility to control and fine tune the crystalline structure, porosity, chemical environment and functionalities of the material.…”
Section: Introductionmentioning
confidence: 99%
“…There is much interest in the design of hybrid materials for selective and multi-step catalytic processes 1 . In this field, Metal-Organic Frameworks (MOFs) can play an important role due to the possibility to control and fine tune the crystalline structure, porosity, chemical environment and functionalities of the material.…”
Section: Introductionmentioning
confidence: 99%
“…For this reaction, the acid-base pairs work in a concerted way to activate simultaneously the two reactants, as was previously shown with other inorganic and organic catalysts with acid-base pairs. [15][16][17][18] . Similarly, Wu et al 13 prepared a lanthanide MOF containing Lewis acid Tb 3+ and Lewis base triphenylamine sites, and used it for Knoevenagel an cyanosylalation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…38 It has been reported that the alkylation mainly occurs on the external surface of MWW and because of that a new type of 2D layered zeolite with well structured and very large external surface area were developed by delamination of a laminar precursors of different zeolites. 39,40,41 In the case of the laminar precursor of MWW, the 2D layered zeolite ITQ-2 was prepared in where the 12R hemicavities similar to cups are exposed to the exterior ready to adsorb-react-desorb without requiring diffusion through micropores 42 (see Figure 12 and Figure 1 Supporting information). Since this material with external surface areas larger than 600 m 2 /g was shown to be more active for alkylation of biphenyl with propene than the corresponding 3D MWW zeolite, 43 we have studied here, the catalytic behavior of ITQ-2 for alkylation of toluene with HMF.…”
Section: D Layered Zeolites As Alkylation Catalyst For Toluene With Hmfmentioning
confidence: 99%